Simulasi Distribusi Fluks Magnet oleh Pengaruh Konfigurasi Stator Rotor pada Generator Aksial dengan Software FEMM 4.2 - , NOBAL ARDHINATA RAHADYAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Axial Machine has magnetic flux in the same direction with its rotational axis so that stator and rotor can be installed in axial direction. This machine has a compact and modular construction causing axial machine is much more flexible. The use of rare-earth permanent magnets such as NdFeB, SmCo, and others which have a large remanent and coercivity so these can replace excitation windings on the rotor. This paper aims to look at the distribution pattern of the magnetic topology resulting from the second axial machine. The simulation was performed with the finite element method software FEMM 4.2 using symmetry analysis which considers all parts of identical geometry. In this software will see the pattern of the magnetic flux distribution as well as the effects on axial machine. The output obtained from the magnetic flux distribution pattern can be either air-gap magnetic flux density, anchor reaction flux density, induced electromotive force and the electromagnetic torque generated.